Cuantificación del transcripto BCR-ABL1 relativo a diferentes genes control: ABL1 y GUSB en pacientes con leucemia mieloide crónica - Paggi D'Agostino, Andrés (2017)
To evaluate the expression levels of the BCR-ABL1 rearrangement in Chronic Myeloid Leukemia, it is used ABL1 as control gene. Taking into account that this gene is involved in the translocation, others genes have been postulated, including beta-glucuronidase (GUSB) that is located on the long arm of chromosome 7 and it is not involved in the BCR-ABL1 rearrangement. In the present study three parameters of early molecular response were evaluated: 1. Level of transcripts on an international scale at three months; 2.- Reduction of transcripts to achive half of the baseline value (Halving time) with both control genes; 3.- Logarithmic reduction at three months of treatment (using the GUSB control gene). Through the real-time polymerase chain reaction all involved transcripts (BCR-ABL1, ABL1 and GUSB) were quantified and a conversion factor for GUSB was calculated to validate the results on an international scale. Forty-four patient samples were studied at diagnosis, 18 at three months and 11 at six months of follow-up of the disease under treatment with tyrosine kinase inhibitors (TKI). Analyzing the means of transcripts-BCR-ABL1 at diagnosis, at 3 and 6 months, it was observed that at diagnosis the BCR-ABL1/GUSB ratio presented lower values respect to BCR-ABL1/ABL1, whereas at 3 and 6 months the values were coincident. A positive correlation was observed between the level of GUSB and BCR-ABL1 transcripts which could explain the results with GUSB at diagnosis. The decrease in BCR-ABL1 transcripts at 3 months and 6 months from the time of diagnosis was greater using the ABL1 control gene than with the GUSB control gene. The rate of reduction of BCR-ABL1 transcripts (Halving time) was evaluated with both control\n7\ngenes. ROC curves were performed, obtaining cut off values of ? 26 days for GUSB and ? 23 days for ABL1. With this analysis, in addition, it was observed that ABL1 has greater discrimination power than GUSB between responders and non-responders. Using the Fisher test applied to the data obtained with the ABL1 control gene, we observed that the Halving time ? 23 days was associated with a Major Molecular Response at 12 months of treatment. Our data indicate that ABL1 allows to discriminate with greater sensitivity the response to the treatment with TKIs compared to GUSB.